PELATIHAN DIGITALISASI MATERI SEJARAH LOKAL RIAU MELALUI BUKU DIGITAL BAGI GURU SEJARAH DI KEC. RENGAT KAB. INDRAGIRI HULU - Bunari, Bunari; Hasibuan, Rizki Ananda; Fikri, Yanuar Al; Syhaputra, Muhammad Afrillyan Dwi; Ramona, Nadia; Rafianti, Ria (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Currently, the transformation of physical local history material into digital form is becoming an attraction for history learning. Apart from providing new experiences to students, digitalization is also a means of responding to the challenges of globalization where the trend is moving towards paperless teaching materials. One of the solutions offered is to provide training in creating digital books based on flip builder pro which will produce a book display that can be accessed easily and can be downloaded for free by students just by